Emotional Intelligence and Leadership Personality for Managers - عبد سلمان, ناظم جواد (Journal of Economics and Administrative Sciences, 2012)
The purpose of this research is to analyze the relationship between the emotional intelligence and the leadership personality of the managers . the research was tested at the college of administration and economics – university of Baghdad through applying it on a sample of (67) members and units of the college. a questionnaire was used as a major tool for collecting data and information . for the purpose of researching to conclusion, the research aimed to test two main hypotheses related to the correlation coefficient and the effect correlation between the two main variable of the research, some statistical techniques such as (the mean, student deviation, percentages, correlation coefficient spearman, simple regression) were used for the purpose of researching the data. the research has reuched many conclusion, which was the most important one represented by the rise of the emotional intelligence and the attitudes of the leader personality of the managers , and there were correlation coefficient  between the two main variable, and there was significant effect for the emotional intelligence into the leader personality of the managers ,due to the conclusions reached, the researcher recommands for the necessity of the studied organization to seriowh disclose and enhance the competencies of the emotional intelligence and the attitudes of leadership personality of the managers through its management practices